Intégrer le corps en deuil fragmenté - Carine Plancke (Ateliers d'Anthropologie)
Anthropological studies on lamentations have stressed the obligatory side of this chanted practice and its social consolidation role. But if one turns attention to the experience of the mourner, it seems that the lamentations also serve to remedy the fragmentation provoked by the loss of a loved one. This perspective is adopted in this article dedicated to funeral lamentations among the Punu of Congo-Brazzaville. Through an analysis of the content of lamentations and their stylistic arrangement, it is shown that mourners give voice to their emotions in such a way that the musicality is interrupted, but they always re-establish the musical flow. In this way they restore wellbeing, which is conceptualised among the Punu as a repeated flow. Processes of deepening through repetition and of alternation between appropriation and distancing because of an oscillation between the particular and the general prove to be essential for completing this mourning work.